Translational interdisciplinary research on human chorionic gonadotropin’s enhancement of neuroendocrine crosstalk: a novel medical hypothesis for systemic adjunctive treatment of psychiatric disorders - João Francisco Pollo Gaspary; João Francisco Pollo Gaspary; Luis Felipe Dias Lopes; Antonio Geraldo Camara (Frontiers in Psychiatry)
IntroductionIt is increasingly recognized that the brain continuously interacts with other body systems such as the immune system, the gut-brain axis, and the endocrine system. Dysfunctions in these systems can impact mental health by altering neurotransmitter levels and the neurochemical environment. This shift in understanding underscores the need for therapeutic strategies that address systemic health and mitochondrial function, alongside psychosocial aspects of the disease, offering a more personalized and adaptive approach to treatment.MethodologyThis study utilizes a translational research approach structured through the Work Breakdown Structure methodology, dividing the process into six interconnected Work Packages (WPs). These include systematic literature reviews on endocrine dysfunctions and hormonal therapies in mental disorders, application of Design Thinking for neuroendocrine innovation, and hypothesis exploration of hCG as a systemic adjunctive treatment for psychiatric disorders, culminating in result dissemination and evaluation.ResultsWork The study identified multiple mechanistic impacts of human chorionic gonadotropin (hCG) relevant to psychiatric treatment. Key findings from hCG Hormetic Therapy (HHT) include stimulation of sex hormone production, reduction of insulin resistance and systemic inflammation, enhancement of hypothalamic activity to regulate appetite, sleep, and emotions, and LH-like effects on cognition. HHT also increases IGF-1 availability, promoting neuroprotection, cognitive improvements, and reduced mitochondrial dysfunction, restoring cellular function critical for brain health.Implications for Clinical PracticeThe findings underscore the significance of enhancing endocrine and metabolic functions as a viable strategy for improving psychiatric care, aligning with trends that advocate holistic treatment strategies. The suggested dose for future research protocols is 500 IU IM per week for at least 10 weeks.ConclusionSupporting diverse and varied research is crucial for advancing medical knowledge. Continuous exploration of neuroendocrine dysfunctions in mental disorders using advanced tools from neuroscience, endocrinology, and psychiatry can provide new pathways for more effective and personalized treatments. The study of HHT effects offers insights into complex neuroendocrine interactions, underscoring the potential for innovative therapeutic strategies in psychiatry.